The miR-4739/DLX3 Axis Modulates Bone Marrow-Derived Mesenchymal Stem Cell (BMSC) Osteogenesis Affecting Osteoporosis Progression - Li, Ding; Yuan, Qi; Xiong, Liang; Li, Aoyu; Xia, Yu (Frontiers in Endocrinology, 2021)
Osteoporosis is a complex multifactorial disorder linked to various risk factors and medical conditions. Bone marrow-derived mesenchymal stem cell (BMSC) dysfunction potentially plays a critical role in osteoporosis pathogenesis. Herein, the study identified that miR-4739 was upregulated in BMSC cultures harvested from osteoporotic subjects. BMSCs were isolated from normal and osteoporotic bone marrow tissues and identified for their osteogenic differentiation potential. In osteoporotic BMSCs, miR-4739 overexpression significantly inhibited cell viability, osteoblast differentiation, mineralized nodule formation, and heterotopic bone formation, whereas miR-4739 inhibition exerted opposite effects. Through direct binding, miR-4739 inhibited distal-less homeobox 3 (DLX3) expression. In osteoporotic BMSCs, DLX3 knockdown also inhibited BMSC viability and osteogenic differentiation. Moreover, DLX3 knockdown partially attenuated the effects of miR-4739 inhibition upon BMSCs. Altogether, the miR-4739/DLX3 axis modulates the capacity of BMSCs to differentiate into osteoblasts, which potentially plays a role in osteoporosis pathogenesis. The in vivo and clinical functions of the miR-4739/DLX3 axis require further investigation.